Penerapan Strategi Pembelajaran Everyone Is Teacher Here Untuk Meningkatkan Kreativitas Belajar Siswa - Aminah Harahap; Novi Srikandi Nasution (Gravity Journal, 2022)
This study aims to find out how the effectiveness of learning by applying the everyone is a teacher here learning strategy to the creativity of students at SMP Negeri 1 Angkola Barat for the academic year 2021-2022. The research subjects were students of class VIII-1, totaling 30 students consisting of 15 male students and 15 female students. This learning strategy was carried out in cycles I, II, III, the scores for increasing students' creativity in learning physics were 42.5%, 68.7% and 87.5%. While the achievement of student learning scores from the test results obtained the percentage of students' completeness of 30%, 60% and 80% and the scores of observations of the learning process by the teacher were 59.37%, 75% and 90.6%. Based on the number of students 30 students and the number of questions 15 items obtained r table 0.361. The results of the test validity obtained r count 0.468, the test reliability results 0.426. Meanwhile, the results of the level of difficulty and discrimination test were 0.566 and 0.400. Thus, it can be concluded that the application of the everyone is a teacher here learning strategy can increase the creativity of students in learning physics in class VIII-1 SMP Negeri 1 Angkola Barat for the 2021-2022 academic year.